Genome-wide identification of mononuclear cell DNA methylation sites potentially affected by fish oil supplementation in young infants: A pilot study. (October 2015) - Lind, M.V.; Martino, D.; Harsløf, L.B.S.; Kyjovska, Z.O.; Kristensen, M.; Lauritzen, L.
Abstract: Recent evidence suggests that the effects of n-3LCPUFA might be mediated through epigenetic mechanisms, especially DNA-methylation, during pregnancy and early life. A randomized trial was conducted in 133 9-mo-old, infants who received 3.8 g/day of fish oil (FO) or sunflower oil (SO) for 9 mo. In a subset of 12 children, buffy-coat DNA was extracted before and after intervention and analyzed on Illumina-Human-Methylation 450-arrays to explore genome-wide differences between the FO and SO groups. Genome-wide-methylation analysis did not reveal significant differences between groups after adjustment for multiple testing. However, analysis of the top-ranked CpG-sites revealed 43 CpG׳s that appear modified with an absolute difference in methylation of ≥10%. Methylation levels at these sites were associated with phenotypic changes mainly in blood pressure. In conclusion, our analyses suggest potential epigenome effects that might be associated with functional outcomes, yet the effect sizes were small and should be verified by additional investigation.